Analysis of the Role of the Village Consultative Body in the Village Government System in Indonesia - Anwar Hidayat (Jurnal Sosial Sains dan Komunikasi, 2023)
This research aims to examine the role of the Village Consultative Body (BPD) in the context of the village government system in Indonesia. The Village Consultative Body is an institution that has an important role in decision making at the village level. This research uses a qualitative approach with data collection techniques through in-depth interviews, participant observation, and analysis of related documents. The research results show that the Village Consultative Body (BPD) has a crucial role in the village government system in Indonesia. Through its functions, such as channeling community aspirations, maintaining customs and culture, compiling village regulations, and supervising the performance of village heads, BPD is the main pillar in maintaining the sustainability and welfare of village communities. Although there are challenges in implementing its role, such as a lack of understanding of democratic principles and the potential for conflict between institutions in villages, efforts to strengthen capacity and transparency in village government are very important to increase community effectiveness and participation in local development.